Hubungan dukungan keluarga dan persepsi kesuksesan dengan motivasi berprestasi siswa SMA Negeri 1 Harapan Cemerlang, Kabupaten Banyumas, Jawa Tengah - Wulan Nurrokhmah; Nanang Martono; Agung Kurniawan; Elis Puspitasari (LP2M Universitas Sarjanawiyata Tamansiswa, 2025)
This study explains the relationship between family support and perceived success with high school students' achievement motivation. The method used was a survey in one of the high schools in Banyumas. The population was 715 students from tenth and eleventh grade. In this study, the sample amounted to 392 students who were determined using simple random sampling technique. The results revealed that the Kendall's tau correlation value on the family support variable was 0.13 with a significance value of 0.05. Meanwhile, the perceived success variable showed a Kendall's tau correlation value of 0.28 with a significance value of 0.01. These results indicate a positive relationship between family support and achievement motivation and a positive relationship between perceived success and achievement motivation. The ability of families to provide support can increase children's potential to achieve and achieve success. When parents provide optimal support, it can increase children's achievement motivation because children feel fully supported and valued. On the other hand, perceptions of success also contribute to increasing students' achievement motivation. The perception of success that students believe can provide encouragement to develop their potential so that it has implications for increasing student achievement motivation.